Public Land Management Agencies’ and Nonindustrial Private Forest Landowners’ Perceptions towards Ecosystem Services - Taylor Stein; Namyun Kil; Alexis Frank; Alison E. Adams; Damian C. Adams; Francisco J. Escobedo (EDIS, 2013)
The state of Florida has more than 16 million acres of forestland. From clean air to pulp for paper to aesthetic landscapes, humans benefit from private and public forests in many different ways. However, small private landowners and public land management agencies manage the majority of this land, and it is up to these people to decide how society will benefit from those forests. This paper uses the concept of ecosystem services to explore the reasons why public land management agencies and private landowners manage their forests. This 5-page fact sheet was written by Taylor Stein, Namyun Kil, Alexis Frank, Alison E. Adams, Damian C. Adams, and Francisco J. Escobedo, and published by the UF Department of School of Forest Resources and Conservation, July 2013. http://edis.ifas.ufl.edu/fr380